Micro-Finance as a Triggering Mechanism for Empowering Women’s Entrepreneurship in Sri Lanka - Sumanasiri, Ayoma; Chandrarathna , Prabhavi (Archives of Business Research, 2021)
The Micro-Finance sector has been identified as one of the main sectors that contributes to the eradication of poverty and to empowering women in developing countries. Women’s Entrepreneurship is considered an emerging trend among nations and contributes to the development of a country. It is also identified as an important means to end poverty and therefore, female empowerment through entrepreneurship has been well recognized. Micro-finance enables women’s entrepreneurial success; however, the context of the urban sector has not been well examined in the literature since most scholars perceive that poverty is mainly confined to the rural areas of a country. There are many services provided by the Micro- Finance sector. However, it is vital to identify their impact on Women’s Entrepreneurial success, particularly in the urban sector of the country. Accordingly, this study focuses on examining the impact of Micro-Finance, which includes Micro-Credit, Micro-Savings and Micro-Insurance, on Women’s Entrepreneurial success in Sri Lanka, specifically in the Colombo district. 240 women entrepreneurs who have obtained micro financial services in the Colombo district were used as the sample of this study. In order to arrive at a conclusion regarding the relationship between micro-credit, micro-savings, micro-insurance and entrepreneurial success, a 5-point Likert scale questionnaire has been used. The required data were collected by distributing the questionnaire through Google Forms. The statistical software package SPSS was used to analyze the collected data. It was identified that all the measurement items under Micro-Credit, Micro-Savings and Micro- Insurance exhibit significant relationships with Women’s entrepreneurship in the Colombo District, and therefore, all the hypotheses were accepted. Recommendations are provided to further enhance female presence and success in entrepreneurship in Sri Lanka.